2019
DOI: 10.1016/j.optom.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

High-speed recording of thermal load during laser trans-epithelial corneal refractive surgery using a 750 Hz ablation system

Abstract: The ITEC software is effective in controlling the maximum temperature rise during laser ablation in the extremely challenging situation of trans-PRK involving high ablation volumes of almost 6000nl, potentially improving the outcomes. The ITEC system limited the maximum temperature to 39.7°C in the epithelium, and 37.7°C in the stroma. The epithelial temperature was always higher than stromal temperature (regardless of high or low fluence irradiation). Safety limit of 40°C found in the literature was never rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…The maximum ocular surface temperature during epithelial ablation ranges from 35.2°C to 39.7°C, and during high and low fluence laser stromal ablation ranges from 32.9°C to 36.5°C and from 34.4°C to 37.7°C, respectively. De Ortueta et al 21 concluded that limiting the maximum temperature to below the safety limit of 40°C reported in the literature could decrease the occurrence of postoperative corneal haze. The routine usage of chilled BSS before and immediately after laser ablation, and the time gap of about 10 s between PTK and PRK add a cooling effect to the cornea compensating for heat generated by the excimer laser.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The maximum ocular surface temperature during epithelial ablation ranges from 35.2°C to 39.7°C, and during high and low fluence laser stromal ablation ranges from 32.9°C to 36.5°C and from 34.4°C to 37.7°C, respectively. De Ortueta et al 21 concluded that limiting the maximum temperature to below the safety limit of 40°C reported in the literature could decrease the occurrence of postoperative corneal haze. The routine usage of chilled BSS before and immediately after laser ablation, and the time gap of about 10 s between PTK and PRK add a cooling effect to the cornea compensating for heat generated by the excimer laser.…”
Section: Discussionmentioning
confidence: 97%
“…Transepithelial platforms result in less heat generation at the corneal surface. 21 Effective control of the maximum temperature rise during laser ablation could reduce the incidence of postoperative haze. The baseline ocular surface temperature, immediately prior to beginning excimer laser, ranges from 32°C to 34.9°C.…”
Section: Discussionmentioning
confidence: 99%
“…This spatial and temporal separation of laser pulses minimises the thermal load by allowing time for localised cooling. When tested with the Amaris 750 Hz excimer laser during transPRK, De Ortueta found that this kept the corneal epithelium below the 40deg C safety net thought to be the level at which collagen proteins start to denature [ 47 , 48 ]. Incremental improvements to these treatment normograms have shown improved outcomes with respect to HOAs [ 49 ].…”
Section: Transprk Platformsmentioning
confidence: 99%
“…The incidence of thermally induced haze can be reduced with several methods, including the optimised ablation platforms that reduce the thermal load and leave behind a smoother stromal surface. Intraoperative routine usage of chilled balanced salt solutions and a time gap between epithelial and stromal ablation helps to limit the maximum temperature below the safe threshold of 40 °C, as recommended by De Ortueta [ 47 ], though this does increase the treatment time. Managing the thermal load will also decrease ocular surface pain after the procedure [ 110 ].…”
Section: Issuesmentioning
confidence: 99%
“…Furthermore, the epithelial ablation rate is higher than that of the stroma. 2 As a result, performing trans-PRK to an abnormal epithelial surface could result in subsequent abnormal and unpredictable stromal ablation.…”
mentioning
confidence: 99%